2019
DOI: 10.1111/jcpt.12998
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of the potentially fatal hyperhaemolysis syndrome of sickle cell anaemia with a regimen including bortezomib and Hemopure

Abstract: What is known and objective Hyperhaemolysis syndrome (HHS) of sickle cell anaemia (SCA) is a life‐threatening condition characterized by accelerated destruction of red blood cells typically following blood transfusions. Optimal treatment strategies have not been determined; therefore, reports utilizing novel therapies are needed. Case description A 19‐year‐old African American man with SCA experienced HHS following a partial red cell exchange transfusion. He was treated with methylprednisolone, rituximab, darb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Hemoglobin-based oxygen carrier-201 has been allowed by the FDA for use under the expanded access in Jehovah's Witnesses patients who require blood transfusion. HBOC-201 has no cell membrane and lacks cell surface antigens, making HBOC-201 an ideal substitute for blood to save lives when blood is unavailable or blood transfusion is refused for patients with severe autoimmune hemolytic anemia ( 30 , 32 , 33 , 36 , 37 ). Epperla et al demonstrated that early recognition of patient needs and familiarity with the characteristics of HBOC-201 by clinicians are essential for the safe and timely use of HBOC-201 to save the lives of the patients ( 33 ).…”
Section: Anemiamentioning
confidence: 99%
“…Hemoglobin-based oxygen carrier-201 has been allowed by the FDA for use under the expanded access in Jehovah's Witnesses patients who require blood transfusion. HBOC-201 has no cell membrane and lacks cell surface antigens, making HBOC-201 an ideal substitute for blood to save lives when blood is unavailable or blood transfusion is refused for patients with severe autoimmune hemolytic anemia ( 30 , 32 , 33 , 36 , 37 ). Epperla et al demonstrated that early recognition of patient needs and familiarity with the characteristics of HBOC-201 by clinicians are essential for the safe and timely use of HBOC-201 to save the lives of the patients ( 33 ).…”
Section: Anemiamentioning
confidence: 99%
“…The role of exchange transfusion was believed to be benefi cial as it removes the antibody-coated RBC and circulating bilirubin. Hence, replacing them with RBCs compatible with the patient's serum and providing albumin with new bilirubin binding sites [5,11,19,21]. The role of specifi c immunotherapy has also been described in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…52 In recent years, case reports have described the suc cess ful use of HBOC-201 in the set tings of hyperhemolysis and alloimmunization as well as for Jeho vah's Witnesses, though there were reports of hyper ten sion, elevated liver enzymes, and met he mo glo bi ne mia. [52][53][54] While HBOCs can help to avoid or replace trans fu sion, with out fur ther studies of safety and eff cacy and US Food and Drug Administration approval these agents will have lim ited avail abil ity.…”
Section: Hemoglobin-based Oxy Gen Car Ri Ersmentioning
confidence: 99%